Teaching Object-Oriented Programming: A Comparison Of Java And Objective-C - Koster, Alexis (International journal of management & information systems, 2015)
The programming language Java has been for many years the language in which many Web applications as well as large server applications have been developed. More recently, it has also been used in the development of Android applications. It has often been adopted as the primary teaching language in both introductory and advanced programming courses. Due to its use on the iPhone and the iPad, Objective-C is gaining popularity and is now taught in some programming courses. Not as well designed as Java and not as general-purpose as Java, Objective-C is unlikely to supplant it in college courses.